Comparative evaluation of structured telephone call, WhatsApp text messaging and chewing gum on orthodontic anxiety: a prospective cohort study - Cheong, Joo Ming; Mohd Ibrahim, Mohamad Shafiq (2023)
Background: Anxiety is a significant side effect during orthodontic treatment. Non-pharmacological methods may have an effect in decreasing anxiety level among patients undergoing orthodontic treatment. Purpose: To investigate whether there was a difference in self-reported state anxiety among patients with orthodontic initial aligning archwire placement between postprocedural telephone call, text messaging, chewing gum and control group. Methodology: Eighty female new orthodontic patients were randomly assigned to one of four groups (structured telephone call, WhatsApp text messages follow-up, sugar-free chewing gum and control). Subjects in the first three groups received the interventions after 24 hours of upper and lower 0.014” NiTi archwire placement, and completed the state component in state-trait anxiety inventory (STAI) questionnaire to assess their level of anxiety before archwire placement, immediately after, at 24 hours and daily for seven days. One-way repeated measure ANOVA was conducted to compare the effects of non-pharmacological methods on the mean state anxiety level at different time points. Results: In the experimental groups, state anxiety level peaked at 24-hour following archwire placement. The greatest reduction of anxiety was observed between day-1 (45.70  2.32) and day-2 (39.90  2.22) in chewing gum group. There was significant difference in mean state anxiety level among the four groups at p<.001. Post hoc comparisons revealed significant difference between chewing gum and control groups at day-4 until day-7, and significant difference between WhatsApp text messaging and control groups at day-2 until day-7, as well as between telephone call and control groups at day-4 until day-7. There was significant difference in the mean anxiety level between chewing gum and WhatsApp text messaging group at day-1. At day-7, WhatsApp text message group had the lowest mean state anxiety level (26.85  2.03), followed by chewing gum group (27.10  2.03), telephone group (29.15  2.03) and lastly control group (41.45  2.03). Conclusion: Structured telephone call, WhatsApp text messaging and chewing gum conferred better anxiety reducing effect in patients with initial orthodontic aligning archwire placement compared to no treatment.